Co-occurrence and Diversity of Soil Trichoderma and Fusarium species from Different Land Use Intensities in Machakos County, Kenya - , P. K. Maina, P. M. Wachira, S. A. Okoth, J. W. Kimenju, J. M. Mwangi (Archives of Current Research International, 2016)
Soil fungi are important components of the soil biota and their diversity is a good indicator of soil health. Soil fungi respond differently to land use practices and to their relative populations. The co-occurrence and diversity of Trichoderma and Fusarium species against various land use types (LUTs) was investigated. The genus Trichoderma contains many important species with potential for biocontrol of soil-borne plant pathogens as well as high saprophytic capacity while the genus Fusarium has many species that are highly pathogenic to plants and with potential for mycotoxin production. This research adopted a cross-sectional study design. Soil samples were collected from 3 land-use types (LUTs) in Kabaa irrigation scheme in Machakos County, Kenya, that is, intensive land-uses under irrigation and rain-fed agriculture and undisturbed lands. From the top soil layer, 100 soil samples were collected. The samples were processed and 369 Trichoderma and 1,546 Fusarium isolates recovered. Fusarium had a higher abundance than Trichoderma in the highly disturbed lands. In the undisturbed lands, Trichoderma had a higher abundance than Fusarium. There was a clear negative correlation between Trichoderma and Fusarium occurrence and diversity. The study further revealed that disturbance had a positive effect on Fusarium but a negative one on Trichoderma.